2006
DOI: 10.1086/498977
|View full text |Cite
|
Sign up to set email alerts
|

Are Swine Workers in the United States at Increased Risk of Infection with Zoonotic Influenza Virus?

Abstract: Occupational exposure to pigs greatly increases workers' risk of swine influenza virus infection. Swine workers should be included in pandemic surveillance and in antiviral and immunization strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
178
5
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 23 publications
15
178
5
10
Order By: Relevance
“…With regard to other SIV strains other than A(H1N1)pdm09, previous studies found an increased risk of seropositivity to at least one SIV in pig workers, including H1N1,17, 18, 27, 29, 31, 33, 41, 42, 43 H1N218, 28, 31 and H3N228, 29, 30, 44 strains. In our study, we found increased risk of seropositivity both to swine H1N2 and H3N2 Perth.…”
Section: Discussionmentioning
confidence: 97%
“…With regard to other SIV strains other than A(H1N1)pdm09, previous studies found an increased risk of seropositivity to at least one SIV in pig workers, including H1N1,17, 18, 27, 29, 31, 33, 41, 42, 43 H1N218, 28, 31 and H3N228, 29, 30, 44 strains. In our study, we found increased risk of seropositivity both to swine H1N2 and H3N2 Perth.…”
Section: Discussionmentioning
confidence: 97%
“…They have included serosurveys of bird cullers, open bird market workers, swine workers, duck hunters, meat processing workers, veterinarians and poultry workers, concluding that these populations are indeed at greater risk of infection with zoonotic influenza virus 5 , 6 , 8 , 9 , 10 , 11 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…As per our previous reports, 5 , 6 serum samples were studied for human influenza virus exposure using a hemagglutination inhibition (HI) assay against three recently circulating human influenza virus strains: A/New Caledonia/20/99 (H1N1), A/Nanchang/933/95(H3N2), and A/Panama/2007/99(H3N2). HI titer results were reported as the reciprocal of the highest dilution of serum that inhibited virus‐induced hemagglutination of a 0.65% solution of guinea pig red blood cells.…”
Section: The Studymentioning
confidence: 99%
“…4 This same study showed that the adjusted odds ratio (OR) for swine farmers having an elevated antibody titer to a classic swine H1N1 virus was 35.3 (95% CI 7.7-161.8) in comparison with controls not exposed to swine. 4 In another recent publication, swine workers' high risk (OR = 30.3; 95% CI 3.8-243.5) of elevated antibodies to swine H1N1 virus decreased almost to that of nonexposed controls when the workers reported using gloves during their occupational exposures. 5 We recently validated these cross-sectional study reports with a prospective 2-year study of 803 rural Midwesterners.…”
mentioning
confidence: 93%